Penerapan Metode AHP untuk Prediksi Persiapan Total Ekuitas Year of Year pada Bank - Julio Warmansyah (Universitas Binaniaga Indonesia, 2023)
Banking has its own assessment of the total equity owned by the bank or as the total shares issued per year. This can be predicted using several variables including cash of credit return of assets, return of equity and gross credit. Prediction of this assessment can be developed using linear programming seen with a certain scale of banking assessment starting from 2017 to 2021. The handling of the variables mentioned above can also be arranged using priorities using the process hierarchical analytical method. Multiple linear analysis used to analyze the prediction of shares that will be released on the market predicts shares that can be released on the market based on the variables cash of credit, return of assets, return of equity and gross credit.